Jawetz, Melnick and Adelberg's medical microbiology - Jawetz, Ernest; Adelberg, Edward A.; Melnick, Joseph L. (McGraw Hill Medical, 2010)
An essential overview of the organisms and agents involved in clinical microbiologyThis landmark text now in full-color for the first time describes the organisms and agents involved in clinical microbiology. The book is updated with outstanding learning aids such as 200 USMLE-style review questions, tables, key points, boxed case studies, and chapter objectives and summaries. The companion LANGE site (www.LangeTextbooks.com) features additional review questions, learning aid, and illustrations.